Navigating work, family, and society: Challenges facing Jordanian female journalists - Hana Al-Souob; Enas A Assaf (PLoS ONE, 2026)
The aim of this study is to explore the challenges encountered by Jordanian female journalists, focusing on their experiences in the journalistic work environment (including the workplace and the field) in addition to the challenges faced from society and family. Through using a qualitative and inductive approach by conducting in-depth interviews with Jordanian female journalists who are registered professionals working in a variety of media environments, including daily, weekly, and electronic media. The research findings explore a wide range of challenges female journalists face in Jordan, including workplace issues and external challenges from family and society. The following main themes were emerged in the study, at the workplace level: harassment and newsroom safety; pay inequalities, organizational culture and leadership this point leads to subthemes as bullying, framing female Journalists, and stigmatization, On the other hands challenges themes found at the level of the society and family security which emerged several subthemes as party affiliation, security harassment, and cultural beliefs, as well as family, parents and relatives perspectives. The findings highlight persistent gender‑based discrimination shaped by workplace practices and cultural expectations. Strengthening protections, ensuring fair pay and promotion, and shifting societal attitudes are essential to supporting female journalists. Further research is needed to better understand these challenges and inform effective solutions.